Activity-Based Proteomics of Lipolytic Enzymes - Ruth Birner-Gruenberger; Albin Hermetter (Current Drug Discovery Technologies, 2007)
Lipases play fundamental roles in biological processes since hydrolysis of triacylglycerols and cholesteryl esters is a key event in energy homeostasis of animals. Perturbations in the metabolism and the cellular retention of lipids result in common diseases such as obesity, type 2 diabetes, and atherosclerosis. The introduction of active site-directed chemical probes for enzymatic activity profiling in complex mixtures, known as activity-based proteomics, has greatly facilitated and accelerated global analysis and functional annotation of lipolytic proteins. Here we review probe design and application for discovery and discrimination of lipolytic and esterolytic enzymes. These probes are usually detected by their fluorescent or affinity tags and their protein targets are analyzed using established proteomics techniques. Moreover, microarray technologies can be applied for higher throughput screenings of enzyme or probe specificity.
Keywords: lipases